FUNGSI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Sunardi Sunardi (Manajer Pendididikan, 2015)
the purpose of this research is to describe the function of the headmaster as educator, manager, leader, motivator, and supervisor. This study used the qualitative descriptive method.The echniques for collecting the data were interview, observation, and documentation. The result of this study showed that the headmaster had done the function as educator, manager, leader,motivator, and supervisor to increase the teachers performance,but still not optimal. The suggestion for the education Deapartmen ton give the chance for the headmaster and teachers to increase their professional skill in forward the education world.Keywords: headmaster, performance, teachers.